From lab and up: superior and economic heat transfer performance of ionanofluids containing long carbon nanotubes and 1-ethyl-3-methylimidazolium thiocyanate. (June 2021) - Jóźwiak, Bertrand; Dzido, Grzegorz; Kolanowska, Anna; Jędrysiak, Rafał G.; Zorębski, Edward; Greer, Heather F.; Dzida, Marzena; Boncel, Sławomir
Highlights: Demonstration of long MWCNT-based ionanofluid as the superb heat transfer media Custom-made set-up toward convective heat transfer coefficient / pressure drop Heat transfer of ionanofluids found as dominated by the convection mechanism Pressure drop penalty paid by 48%-higher convective heat transfer coefficient High performance evaluation criterion of 1.26, and efficiency-price index of 1.21 Abstract: The optimization of energy systems and the efficiency enhancement of energy conversion processes are still huge challenges. The ionanofluids (INFs) composed of the long multi-walled carbon nanotubes (MWCNTs) and 1-ethyl-3-methylimidazolium thiocyanate ionic liquid ([C2 C1 im][SCN]) are innovative systems with proven remarkably enhanced thermal conductivity and attractive rheological characteristics. Therefore, as an extension of our previous study, this work aims to examine the overall heat transfer performance of these INFs as working fluids for energy conversion processes and design sustainable energy systems. The new measuring set was designed and constructed to determine the convective heat transfer coefficient and pressure drop during the flow of INFs, using the heat exchanger with saturated steam at 100°C. The obtained results showed that the heat transfer of INFs is prevailed by the convection mechanism. According to a new thermo-economic efficiency-price index proposed in this work, the amalgamation of MWCNTs with [C2 C1 im][SCN] is justified from both thermophysical and economic points of view. Graphical abstract: Image, graphical abstract